Sexual disorders following ob-gyn surgeries - Mazurkiewicz, Dariusz Wojciech; Kobylec, Michał; Zdanowicz, Bogumiła; Marek, Alina (Polish Journal of Public Health, 2013)
It has been known for years that obstetric and gynecological surgeries, apart from bringing measurable health benefits, may also become a factor impairing or improving and sometimes changing patients’ sexual attitudes and sensations. Sexual disorders are a frequent phenomenon resulting from complications following ob-gyn procedures. It is manifested in sexual health anomalies and is corroborated by the prerequisites for the quality of life and intimate aspects of the partners’ sexual life. The development of surgical techniques, the specialization of their specific methods and the application of new materials are expected to minimize the risk of complications in that type of procedures, which should result in a decrease in post-operative sexual disorders. Great significance is attached to therapy individualization, including hormone therapy, which should increase the efficiency of the existing sexual disorder treatment. Attention is also paid to the constructive way of taking the patient’s history in the pre-operative and post-operative period as well as to the process of treatment and healing, by familiarizing the female with the surgical technique, therapeutic procedures and types of any possible complications, among other things. Sexual disorders affecting the mental and physical sensations following obstetric and gynecological surgeries may impact both partners and – not uncommonly – may cause family dysfunctionality or partnership crisis and breakdown.